Сказка о Мальчише- Кибальчише - Гайдар Аркадий Петрович (Внеклассное чтение, 2016)
Экземпляры: ф.9 (20190219) / Инвентарный номер: 56679 / Цена: 91.00 / Авт.знак: Г 14 / ГРНТИ: 17.82 / ББК: 84 (2 Рос=Рус)6